Schopenhauer and the nature of philosophy - Head, Jonathan (Contemporary studies in idealism., 2021)
"What is philosophy? What can philosophy offer us? What brings us to think philosophically? Arthur Schopenhauer's writings offer fascinating answers to these questions that have largely been overlooked until now. In Schopenhauer and the Nature of Philosophy, Jonathan Head explores the surprisingly rich and compelling metaphilosophy that underlies Schopenhauer's work and argues that it offers a vital key to unlocking many of the mysteries that surround his ideas. Schopenhauer understands philosophy as grounded in a deep wonder about life and the world that is universal to the human experience, as well as meeting a fundamental need for both explanation and consolation. This account of the nature of philosophy leads to further important discussions concerning the relationship between philosophy and religion, the value of mysticism, and the possibility of social progress. Through examining Schopenhauer's account of how and why philosophy is done, this book sheds crucial new light on a thinker whose ideas continue to both provoke and inspire"--